2014
DOI: 10.1016/j.bbrc.2014.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Oral supplementation with a combination of l-citrulline and l-arginine rapidly increases plasma l-arginine concentration and enhances NO bioavailability

Abstract: Our data show for the first time that a combination of oral L-citrulline and L-arginine effectively and rapidly augments NO-dependent responses at the acute stage. This approach may have clinical utility for the regulation of cardiovascular function in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 36 publications
2
84
0
Order By: Relevance
“…As previously reported in animal studies, 17,18) this study was useful in terms of confirming the combination effects on plasma L-arginine increase in humans as well as in animals. One possible reason for this combination effect might be due to the inhibiting effect of L-citrulline on arginase, which metabolizes L-arginine to urea and L-ornithine.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…As previously reported in animal studies, 17,18) this study was useful in terms of confirming the combination effects on plasma L-arginine increase in humans as well as in animals. One possible reason for this combination effect might be due to the inhibiting effect of L-citrulline on arginase, which metabolizes L-arginine to urea and L-ornithine.…”
supporting
confidence: 75%
“…17) Intriguingly, we recently discovered, in an animal study, that oral supplementation with a combination of L-citrulline and L-arginine efficiently increases plasma L-arginine concentration and peripheral circulation. 18) However, the effects of this combination on humans have not as yet been investigated. We hypothesized that plasma L-arginine would be increased to a greater extent with a combination of L-citrulline and L-arginine, each at half dosage, than by ingesting each of them singly at full dosage.…”
mentioning
confidence: 99%
“…Combination amino acid therapy also warrants consideration. In an animal model, coadministration of arginine and citrulline resulted in a more rapid increase in plasma arginine levels and marked enhancement of NO bioavailability than supplementation of the single amino acids alone 157 . In a murine model, glutamine supplementation improved bioavailability of glutamine and arginine in the fetal plasma and placental fluids 158 .…”
Section: Methods Of Providing Conditionally Essential Amino Acidsmentioning
confidence: 99%
“…A rodent study showed that a combination of L‐citrulline and glutathione supplementation was more effective in increasing the plasma NOx concentration than supplementing with L‐citrulline alone (McKinley‐Barnard, Andre, Morita, & Willoughby, ); therefore, the synergism between NO donor and antioxidants could be a strategy to enhance the NO related vasodilation function in lactating sows. Besides, a combination of half dosage of L‐citrulline and half dosage L‐arginine was more effective in increasing plasma NOx concentration and enhancing vasodilation than separately supplemented with a full dosage of L‐citrulline or L‐arginine (Morita et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The sows were fed either the control diet ( n = 111) or L‐citrulline diet ( n = 110) upon entry to the farrowing house (6 ± 1.8 days [mean ± SD ] before farrowing) until weaning (26 ± 1.5 days lactation). The dosage of the L‐citrulline used in this experiment is based on an experiment by Morita et al, () in the rabbit model, whereby 0.50 g/kg (body weight) via gavage numerically increased the ear blood flow by approximately 7%. Sows were restrict fed 2.5–4 kg from entry until day 3 after farrowing and then fed ad libitum as previously described (Liu et al, ).…”
Section: Methodsmentioning
confidence: 99%